Comparison of Kneelax and KT-1000 Knee Ligament Arthrometers - Paine, Russ; Lowe, Walter (The Journal of Knee Surgery, 2012)
Two commercially available knee ligament arthrometers (KT-1000 MEDmetric Corporation, San Diego, California and Kneelax MR Systems, Haarlem, The Netherlands) were used to measure anterior tibial translation. In this study 91 subjects with no history of knee pathology were tested using both devices. Both normal knees were tested and comparison of recorded anterior translation (millimeters) was performed. Absolute numbers at forces of 67N, 89N, 134N, and manual maximum displacements were recorded. Side-to-side differences were calculated and data were compared. There was a significant difference found between the absolute values of each device. The KT-1000 was found to record greater values in millimeters of translation. Although the absolute values were significantly different, the side-to-side differences were not significantly different between devices.
Keywords: anterior cruciate ligament; translation